PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE TERHADAP PERUSAHAAN PERTANIAN - Elda Sagitarius; Siti Nuridah (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
Tax is the foundation of Indonesia's State Revenue and Expenditure Budget (APBN). The government uses tax revenues as a tool to routinely finance national development. For companies, tax is a burden that will reduce a company's net profit. It is this difference in interests that causes taxpayers to reduce the amount of payments, not even a little from taxpayers who try to avoid the obligation to report and pay their company taxes. This form of tax avoidance by minimizing the legal tax payable is called Tax Avoidance. Tax avoidance is carried out by companies with the aim of diverting funds intended to pay taxes instead allocated to pay company debts. The purpose of this study was to determine the effect of Return On Equity (ROE) and Leverage on Tax Avoidance in agricultural companies. The sampling technique uses purposive sampling with the criteria of agricultural sector companies that do not present complete financial reports for the period 2018 to 2021. The analytical method used is multiple linear regression, hypothesis testing uses the T test to find out the partial regression coefficient and F test to find out the coefficient simultaneous. The results of the study on the T test showed that the Profitability variable proxied by Return On Equity (ROE) had a significant effect on Tax Avoidance. The results of the F test show that the variables Return On Equity and Leverage simultaneously have a positive effect on Tax Avoidance. Leverage proxied by Debt to equity ratio (DER) Has effect on Tax Avoidance.